Perlindungan Hukum Bagi Pelaku Usaha dan Konsumen serta Tanggung Jawab Pelaku Usaha untuk Mempermudah Transaksi Jual Beli dalam Sistem Perdagangan Online - Mario Lengkong; Sinari Telaumbanua; Herlin Herlin; Nobertus Randa Lembang; Siti Nur Atasya (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The development of information technology has encouraged the rapid growth of online trading systems, which facilitate interaction between business actors and consumers. However, this progress also poses new legal protection and challenges to responsibility in electronic transactions. Legal protection for consumers and business actors is regulated by various regulations, such as Law Number 8 of 1999 concerning Consumer Protection (UUPK) and Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE). Consumers are protected from harmful practices, such as inappropriate product information, fraud, or defective products, while business actors are given legal certainty in running their businesses. The responsibilities of business actors include providing clear information, transparent transaction management, and fair dispute resolution. By ensuring clear legal protection and liability, the online trading system can create trust between business actors and consumers, so buying and selling transactions can run more easily, safely, and efficiently. This paper analyses the legal aspects that protect both parties while highlighting the obligations of business actors to create a safe and comfortable transaction environment.